Penerapan Permainan Ular Tangga Edukatif untuk Meningkatkan Pengetahuan Perilaku Hidup Bersih dan Sehat - Pipit Festi Wilianarti; Supatmi Supatmi; Priadi Priadi; Yuanita Wulandari; Musa Ghufron (Journal of Telenursing (JOTING), 2026)
This study aims to determine the effectiveness of the educational snakes and ladders game in improving first-grade students' understanding of Clean and Healthy Living Behavior (PHBS) at MI Al-Munawwaroh Maor. The method used was a descriptive case study involving 15 first-grade students. The results showed a significant increase in student understanding, where before the intervention, 70% of students were in the low knowledge category, and after the intervention, 70% moved to the good knowledge category. Furthermore, students demonstrated enthusiasm, focus, and active participation during the learning process. In conclusion, the educational snakes and ladders game has proven effective in improving PHBS knowledge and can be used as a fun alternative method for health education in elementary schools.   Keywords: Knowledge, Educational Game, PHBS, Snakes and Ladders